2014
DOI: 10.1016/j.bpg.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids, obesity, and the metabolic syndrome

Abstract: Bile acids are increasingly recognized as key regulators of systemic metabolism. While bile acids have long been known to play important and direct roles in nutrient absorption, bile acids also serve as signaling molecules. Bile acid interactions with the nuclear hormone receptor farnesoid X receptor (FXR) and the membrane receptor G-protein-coupled bile acid receptor 5 (TGR5) can regulate incretin hormone and fibroblast growth factor 19 (FGF19) secretion, cholesterol metabolism, and systemic energy expenditur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(152 citation statements)
references
References 101 publications
(131 reference statements)
2
148
1
1
Order By: Relevance
“…LysoPCs can mediate many cell-signaling pathways in monocytes/macrophages 29,31 and specific receptors 32 , and therefore participate in the inflammatory response. In our results, several lysoPC species (LPC C20:4, LPC C18:3, LPC C20:5, LPC C20:3) were down-regulated from pre-DM to NGR group, while the plasma level of LPC C18:1 were higher and LPC C18:0 were lower in DM than pre-DM patients, possibly owing to altered activity of phospholipase A2 which catalyzes PC hydrolysis to lysoPC 33 .…”
Section: Discussionmentioning
confidence: 99%
“…LysoPCs can mediate many cell-signaling pathways in monocytes/macrophages 29,31 and specific receptors 32 , and therefore participate in the inflammatory response. In our results, several lysoPC species (LPC C20:4, LPC C18:3, LPC C20:5, LPC C20:3) were down-regulated from pre-DM to NGR group, while the plasma level of LPC C18:1 were higher and LPC C18:0 were lower in DM than pre-DM patients, possibly owing to altered activity of phospholipase A2 which catalyzes PC hydrolysis to lysoPC 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids are now recognised to have effect beyond the absorption of fats, fat soluble vitamins and cholesterol metabolism by having a broader influence on obesity, type 2 diabetes and features of the metabolic syndrome (Lefebvre et al, 2009;Ma and Patti, 2014). Primary bile acids, synthesised from cholesterol in the liver, are stored in the gallbladder and secreted into the second part of the duodenum in response to a meal.…”
Section: Bile Acid Handling Following Bariatric Surgerymentioning
confidence: 99%
“…Primary bile acids, synthesised from cholesterol in the liver, are stored in the gallbladder and secreted into the second part of the duodenum in response to a meal. Bile acids are actively and passively absorbed in the terminal ileum and effectively recycled via the portal vein to the liver where they may be secreted again into the bile, an enterohepatic cycle that can be completed many times a day (Ma and Patti, 2014). The bile acid pool is self-regulated largely through the nuclear farnesoid X receptor (FXR) and a number of additional feedback pathways.…”
Section: Bile Acid Handling Following Bariatric Surgerymentioning
confidence: 99%
“…Several studies have shown that plasma BAs increase after Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (811). Because BAs can act in an endocrine fashion to regulate a variety of glucose and lipid metabolic pathways (1215), it has been speculated that increased BAs may contribute to at least some of the metabolic improvements after surgery (16,17). Indeed, it was recently shown that the BA receptor farnesoid X receptor (FXR) is required for metabolic improvements in mice subjected to sleeve gastrectomy (18).…”
Section: Introductionmentioning
confidence: 99%